1994
DOI: 10.1083/jcb.125.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional architecture of chromatin in situ: electron tomography reveals fibers composed of a continuously variable zig-zag nucleosomal ribbon.

Abstract: Abstract. The three dimensional (3D) structure of chromatin fibers in sections of nuclei has been determined using electron tomography. Low temperature embedding and nucleic acid-specific staining allowed individual nucleosomes to be clearly seen, and the tomographic data collection parameters provided a reconstruction resolution of 2.5 nm. Chromatin fibers have complex 3D trajectories, with smoothly bending regions interspersed with abrupt changes in direction, and U turns. Nucleosomes are located predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(154 citation statements)
references
References 43 publications
10
143
0
1
Order By: Relevance
“…S6b). However, despite this broad conformational variation, the resulting nucleosome chain folds into an energetically stable fiber with uniform diameter of 31-33 nm consistent with the diameters and extended stiff conformations of long chromatin fibers revealed by ultrastructural analysis in vitro and in situ (11,17,23). Thus, our modeling and experimental approaches both converge to reveal a principle of chromatin fiber organization that reconciles the 2-start zigzag topology with linker DNA bending in one heteromorphic chromatin fiber structure.…”
Section: Internucleosomal Interactions Mapping By Emanicmentioning
confidence: 80%
See 2 more Smart Citations
“…S6b). However, despite this broad conformational variation, the resulting nucleosome chain folds into an energetically stable fiber with uniform diameter of 31-33 nm consistent with the diameters and extended stiff conformations of long chromatin fibers revealed by ultrastructural analysis in vitro and in situ (11,17,23). Thus, our modeling and experimental approaches both converge to reveal a principle of chromatin fiber organization that reconciles the 2-start zigzag topology with linker DNA bending in one heteromorphic chromatin fiber structure.…”
Section: Internucleosomal Interactions Mapping By Emanicmentioning
confidence: 80%
“…Because DNA conformation in chromatin and nucleosome packing are intimately connected to DNA/protein recognition and gene regulation, there has been intense interest in understanding chromatin structure, energetics, and dynamics. Some experimental studies have suggested that nucleosomal arrays fold in a zigzag arrangement with relatively straight linkers and a 2-start nucleosome interaction pattern that brings each nucleosome in proximity to its second nearest neighbor (7)(8)(9)(10) consistent with chromatin fibers observed in situ (11). Other evidence suggests that chromatin condensed with linker histones and divalent cations such as Mg 2ϩ can form either zigzag structures with various nucleosome topologies (12,13) or solenoid-like arrangements.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to early EM images 3 a 2‐start structure is supported by Fourier analysis of images of chromatin fibres 2, chemical cross‐linking 4, the crystal structure of a tetranucleosome 5, cryo‐EM of native fibres 6, cryo‐EM structures of reconstituted fibres containing up to 24 nucleosomes 7 and cryo‐tomographic analysis of native chromatin 8, 9. Nevertheless, early studies on various native chromatin samples by photochemical dichroism 10 and X‐ray diffraction 11, 12, revealed, respectively, a small tilt of the nucleosomal disc relative to the fibre axis and narrow diffraction arcs at 110 Å.…”
Section: Tablementioning
confidence: 99%
“…There is now compelling experimental evidence that the '30-nm' fiber can adopt a 2-start structure. In addition to early EM images (Woodcock et al 1984), a 2-start structure is supported by Fourier analysis of images of chromatin fibers (Williams et al 1986), chemical crosslinking (Dorigo et al 2004), the crystal structure of a tetranucleosome (Schalch et al 2005), cryo-EM of native fibers (Bednar et al 1998), cryo-EM structures of reconstituted fibers containing up to 24 nucleosomes (Song et al 2014), and cryo-tomographic analysis of native chromatin (Horowitz et al 1994;Scheffer et al 2011). Nevertheless, early studies on various native chromatin samples by photochemical dichroism (Sen et al 1986) and X-ray diffraction (Widom and Klug 1985; revealed, respectively, a small tilt of the nucleosomal disc relative to the fiber axis and narrow diffraction arcs at 110 Å.…”
Section: -Nm Fibermentioning
confidence: 99%